Microcomputers and Literacy Project. Final Report - Bruce, Bertram; Michaels, Sarah; Harvard Univ., Cambridge, MA. Graduate School of Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1987)
This is the final report of the Microcomputers and Literacy Project, which was primarily concerned with sociolinguistic analysis of written texts and classroom discourse from two urban, sixth-grade classrooms using computers with QUILL writing software. The report argues for and illustrates an approach to the study of writing that integrates ethnographic analysis of classroom interaction with linguistic analysis of written texts and teacher/student conversational exchanges. The authors use as an analytic construct the notion of a classroom writing system to explore relationships among classroom context, computer-based innovations, writing practices, and actual texts. The report of the two-year study is divided into six sections: (1) definitions and development of the construct of a classroom writing system; (2) description of writing systems in the classrooms studied; (3) use and meaning of the computer, including the function of the computer, student expertise, social interaction, amount and kind of writing produced, gender and ability differences, and teacher attitude; (4) interpretive analysis of individual texts bringing together ethnographic, conversational, and textual data and the interactions that influenced them; (5) conflicting purposes within classroom writing systems, including stated purposes, school purposes, and student purposes; and (6) implications for equity, writing instruction, evaluation of innovations, and teacher education. (Contains 40 references.) (KRN)
Sponsoring Agency: Spencer Foundation, Chicago, IL.
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC. Office of Research.
Contract Number: G-83-0051.
Contract Number: OEG-0087-C1001.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Classroom Environment; Computer Assisted Instruction; Courseware; Definitions; Educational Innovation; Ethnography; Grade 6.; Intermediate Grades; Sex Differences; Sociolinguistics; Teacher Attitudes; Teacher Student Relationship; Writing Instruction; QUILL (Computer Software); Purpose (Composition) -- Writing Samples; Reports, Descriptive